Niketas Choniates - Simpson, Alicia.
1 online resource (389 pages)
Keywords: Simpson uncovers the complex manuscript tradition and transmission of Niketas Choniates' History, an important historical Byzantine text. Investigating issues related to historical narrative and imperial biography, the volume explores the historian's sources and the literary models and historical concepts which guided him.